The Constructivist Approach: Radical and Social Constructivism in the Relationship by Using the Implementation Career Level on the Vocational Education - Haryadi, Haryadi; Iskandar, Iskandar; Nofriansyah, Dicky (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2016)
Vocational education is oriented to the secondary educational in which focusing on the development of the student in order to be ready to work professionally and ready to improve their self-potential, in particular, field work. The aim of this paper is to analyze the constructivist approach to vocational education, the relationship between radical and social constructivist and the implementation of the career level on the voced. The result of this discussion to explain the relationship between radical constructivism and social constructivism is viewed the strong abilities. Radical constructivism related the construction mental structure and meaning by individual. After studying, the social constructivism is more focused the social interaction than the individual knowledge construction, the stressing of construction is shown about the meaning in the social interaction activities. Implementation would be successful about the career in the vocational education and needed the educators to make an active facilitator, particularly to guide the students by question with their assumptions and trained the students by reconstructing the new meaning of knowledge, so that students can be a good career.